Pengaruh Kecerdasan Intelektual Dan Kecerdasan Emosional Terhadap Kinerja Karyawan - Christien Karambut; Jacob Tateol Silangen Makapedua; Daisy Iriany Erny Sundah; Grace Joice Silvana Neltje Rumimper (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2023)
One way to produce good employee performance is to have adequate intellectual intelligence. Employee performance is influenced by ability. Ability is not only about knowledge but also skills. Ability in the form of knowledge can be formed through education and experience, while skills are formed from exercises. One of the skills that employees can manage themselves is emotional intelligence. EmotOne way to produce good employee performance is to have adequate intellectual intelligence. Employee performance is influenced by ability. Ability is not only about knowledge but also skills. Ability in the form of knowledge can be formed through education and experience, while skills are formed from exercises. One of the skills that employees can manage themselves is emotional intelligence. Emotional intelligence can help someone in using their cognitive abilities (knowledge) according to their maximum potential. Emotional intelligence needs to be developed in order to have a positive impact on improving employee performance. The purpose of this study was to determine the effect of intellectual intelligence and emotional intelligence on employee performance either partially or simultaneously. The sample in this study were graduates of the Manado State Polytechnic Department of Business Administration which collected 114 respondent. The sampling technique used convenience sampling and data analysis with multiple regression using SPSS. The results showed that there was a significant influence between intellectual intelligence on employee performance and emotional intelligence on employee performance partially. In addition, intellectual intelligence and emotional intelligence simultaneously affect employee performanceional intelligence can help someone in using their cognitive abilities (knowledge) according to their maximum potential. Emotional intelligence needs to be developed in order to have a positive impact on improving employee performance. The purpose of this study was to determine the effect of intellectual intelligence and emotional intelligence on employee performance either partially or simultaneously. The sample in this study were graduates of the Manado State Polytechnic Department of Business Administration which collected 114 respondent. The sampling technique used convenience sampling and data analysis with multiple regression using SPSS. The results showed that there was a significant influence between intellectual intelligence on employee performance and emotional intelligence on employee performance partially. In addition, intellectual intelligence and emotional intelligence simultaneously affect employee performance